STUDENTS' PERCEPTIONS OF THE IMPLEMENTATION OF TEACHING STRATEGIES IN THE TRANSLATION SUBJECT - Fitria, Rini; Taqiyuddin, Taqiyuddin; Destianingsih, Arita (INOVISH JOURNAL, 2024)
Transferring knowledge to pupils is one of a teacher's most important responsibilities when it comes to teaching. Due to its ability to assist students in overcoming the challenge of translation competence, the blank technique is perceived as one of the research's lessons. Ideas are transferred from the source language to the target language during translation, and the meaning remains the same. For students to learn through the lecture method and to comprehend the content, translation is therefore crucial to the process of learning. A qualitative method was used for this study. Then the research instruments used questionnaires and interviews. The total number of respondents is 13 English Language Education students from STAIN Bengkalis. According to the findings, the majority of students appreciate and benefit from lecturing on the teaching technique. It demonstrated that children study translation because it is enjoyable for them and makes it easier to understand words and sentences. Students who learn translation can help them organize the meaning methodically and increase their knowledge, particularly vocabulary, understanding the text's point of view, and comprehending the text's meaning. It signifies that the teaching technique used in translation class was acceptable and increased students' translation skills. While the results from the interview in this study also revealed that students enjoyed learning translation subjects in order to develop their grasp of the meaning of a text, competence in translating a text, and competence in comprehending English language.